GERAKAN ALIANSI LAKI-LAKI BARU: MEMBONGKAR KONSTRUKSI MASKULINITAS UNTUK MEWUJUDKAN KEADILAN GENDER - Ira Larasati; Pudji Astuti (Journal of Politic and Government Studies, 2019)
This research aims to obtain in-depth information about the New Men Alliance’s movements in dismantling the construction of masculinity in Indonesia as an effort to manifest the gender equity. The research method used in this study is descriptive qualitative. The instruments that used in this research are document studies and interviews conducted to activists of the New Male Alliance. The results of this study shows that male involvement in the feminist movement is needed and has good impact on efforts to transform men from the traditional perspective of the construction of masculinity. The movement carried out by the New Men's Alliance is a movement that focuses on efforts to transform men and form a